A hundred houses: the story of Irene Rowley - Rayment, Anne (Christian Focus Publications, 1991)
January 1966, adventure -- 1938-1954, the perfect family -- 1954-1965, learning for life -- 1962-1965, preparing for service -- 1966, language school, Belem -- 1966, Cameta -- 1967-1968, Cameta -- 1968-1969, Cururupu -- 1971-1975, Portel -- 1976-1980, Portel -- 1981-1984, Belem -- 1984-1990, Belem -- 1990, Ramates -- Looking back and looking forward -- Questions to a missionaries' child -- Some questions to Irene and Joe